Wound healing potential by hyaluronate gel in streptozotocin-induced diabetic rats - Al Bayaty, F.; Abdulla, M.; Abu Hassan, M.I.; Masud, M. (Academic Journals, 2010)
This study was conducted to investigate whether topical application of Hyaluronate gels could improve the impaired wound healing in streptozotocin-induced diabetic rats. Four groups of adult male Sprague Dawley rats, 2 cm full-thickness skin wound were experimentally created on the posterior neck area of streptozotocin-induced diabetic rats (STZ). Wounds of Group 1 animals were topically treated with the vehicle, gum acacia in normal saline, as a placebo control group. Group 2 animals served as reference standard and treated topically with Intrasite gel. Animals of Group 3, 4 were treated topically with new oral high molecular weight hyaluronic acid 240 mg/100 g gel, 0.8% hyaluronic acid gel respectively. Macroscopically, the reference standard gel and the three gels-treated wounds were significantly healed faster in comparison to placebo control wounds group. Wound closure was significantly accelerated by topical application of high molecular weight hyaluronic acid compared to reference standard gel, 0.8% hyaluronic acid gel. Furthermore, histological examination of healed wounds with reference standard gel, 0.8% hyaluronic acid gel, and hyaluronic acid 240 mg/100 g gel-treated wounds revealed comparatively increases in macrophages, fibroblast migration, collagen regeneration, and epithlization compared with the placebo control group. In conclusion, the new oral high molecular weight hyaluronic acid gel can improve the impaired healing of diabetic wounds and could be useful in treating oral ulcerations.